Interactions of Novel Sets of Naphthalene Diimides with G – Quadruplex Structures in Human DNA - Özbil, Ertuğrul (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The discovery of naphthalene diimide derivatives ability to intercalate DNA and stabilize G – quadruplex structures have drawn interest for investigations. Binding affinities of different NDI derivatives to these DNA assemblies depend on various parameters including the planar structure of ligand and attractive molecule. Here we present the interaction of N,N’-bis(4-sulfophenyl)-1,4,5,8-naphthalene diimide with G – quadruplex DNAs such as telomeric DNA (a-coreTT) & non – telomeric DNA (c-myc). The interactions of the ligand with different types of oligonucleotides were measured by UV – Vis spectroscopy & emission spectroscopy. Additionally, a polymerase chain reaction amplified region of the human beta globin gene was used to confirm the formation of G – quadruplex structures within human DNA via gel electrophoresis method. Absorption and emission spectroscopy measurements have indicated notable variations between pure compound and the complexes of compound & oligonucleotide. Moreover, gel electrophoresis results have displayed significant difference between the PCR amplified product alone and PCR amplified product with the ligand where the complex migrated slower. Therefore, the examined S-NDI is a promising DNA – binding ligand within the human genome which requires further investigations to understand the reliability and stability of this particular NDI derivative as DNA – binding ligand. Keywords: Naphthalene diimide derivative, G – quadruplex, human beta globin gene, telomeric region, non – telomeric region

ÖZ: Naftalin diimit türevlerinin DNA’ya bağlanma ve G – dörtlüsü yapılarını stabilize etme kabiliyetinin keşfi, bu tarz araştırmalara olan ilgiyi arttırmıştır. Farklı NDI türevlerinin bu DNA yapılarına bağlanma eğilimleri, hem NDI türevlerinin hemde bu DNA yapılarının düzlemsel yapıları dahil olmak üzere, çeşitli parametrelere bağlıdır. Burada, N,N’-bis(4-sulfophenyl)-1,4,5,8-naftalin diimidinin, telomerik bölgede bulunan DNA (a-coreTT) ve telomerik bölgede bulunmayan DNA (c-myc) gibi G – dörtlüsü yapılarına sahip DNA’lar ile olan etkileşimini gösteriyoruz. Bu türevin bahsedilen farklı oligonükleotit tipleri ile olan etkileşimlerini, UV – Vis spektroskopisi & emisyon spektroskopisi ile ölçülmüştür. Ek olarak, insan beta globin geninin polimeraz zincir reaksiyonu ile çoğaltılmış bir bölgesi, insan DNA’sındaki G – dörtlüsü yapılarının oluşumunu kanıtlamak için jel elektroforez metodu kullanılmıştır. Absorpsiyon ve emisyon spektroskopisi ölçümleri, tek başına ölçülmüş olan bileşik ve bileşik & oligonükleotit kompleksleri arasında kayda değer farklılıklar olduğunu göstermiştir. Ayrıca, jel elektroforez sonuçları, sadece polimeraz zincir reaksiyonu ürününün ve bu ürün ile bileşikten oluşan kompleksten daha hızlı gittiği görülmüştür. Bu nedenle, incelenen S-NDI insan genomunda DNA’ya bağlanabilme özelliği umut verici olan bir bileşiktir ama bu bileşiğin DNA’ya bağlanma özelliğinin güvenilirliğini ve istikrarını anlamak daha fazla araştırma gerektirmektedir. Anahtar Kelimeler: Naftalin diimit türevi, G – dörtlüsü yapıları, insan beta globin geni, telomerik bölge, telomerik olmayan bölge
Master of Science in Chemistry. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2019. Co-Supervisor: Assoc. Prof. Dr. Şükrü Tüzmen, Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry; Perylene dyes; Novel Sets Naphthalene Diimides; Naphthalene diimide derivative; G – quadruplex; human beta globin gene; telomeric region; non – telomeric region